The Meaning of Mekakauhe Language in the Marriage Customs of the Sangihe Tribe: Makna Bahasa Mekakauhe Dalam Adat Perkawinan Suku Sangihe - Daice Daloma; Isnawati Lydia Wantasen; Ivan Robert Bernadus Kaunang; Dwianita Conny Palar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The regional language in the traditional marriage of the Sangihe tribe is an integral part of the cultural heritage of this tribe in Indonesia. This language reflects the values, norms, and traditions that are deeply rooted in the marriage process of the Sangihe tribe. In this study, the researcher explored the important role of traditional languages in Sangihe wedding ceremonies, this study shows that the regional language of Sangihe weddings has an important role in guiding and celebrating the marriage process. The language includes unique phrases, prayers, and speaking procedures that honor traditions and ancestors. The role of this language in maintaining family unity, respect for ancestors, and social responsibility is very important. However, in the face of changing times and global influences, the traditional language of Sangihe weddings faces the risk of declining use. Efforts to preserve and maintain this regional language are becoming increasingly important to connect the younger generation with their cultural roots.